2013
DOI: 10.1021/om400187v
|View full text |Cite
|
Sign up to set email alerts
|

Steric and Electronic Effects in the Formation and Carbon Disulfide Reactivity of Dinuclear Nickel Complexes Supported by Bis(iminopyridine) Ligands

Abstract: We are developing bimetallic platforms for the cooperative activation of heteroallenes. Toward this goal, we designed a new family of bis(iminopyridine) ((N,N′-1,1′-(1,4-phenylene)bis(N-(pyridin-2-ylmethylene)methanamine) and N,N′-1,1′-(1,4-phenylene)bis(N-(1-(pyridin-2-yl)ethylidene)methanamine)) dinickel complexes, synthesized their CS2 compounds, and studied their reactivity. Bis(iminopyridine) ligands L react with Ni(COD)2 to form Ni2(L)2 complexes or Ni2(L)(COD)2 complexes as a function of the steric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…We have been exploring the coordination chemistry and reactivity of mononuclear and dinuclear complexes with iminopyridine ligands in the activation of small molecules, in particular CS 2 and CO 2 . We have previously reported that the bidentate iminopyridine ligand [NN] enables side-on coordination of CS 2 at square-planar Ni centers, Ni­[NN]­(η 2 -CS 2 ). , However, in spite of the significant elongation of the metal-bound C–S bond, no C–S bond breaking (or C–C bond formation) was observed.…”
Section: Introductionmentioning
confidence: 99%
“…We have been exploring the coordination chemistry and reactivity of mononuclear and dinuclear complexes with iminopyridine ligands in the activation of small molecules, in particular CS 2 and CO 2 . We have previously reported that the bidentate iminopyridine ligand [NN] enables side-on coordination of CS 2 at square-planar Ni centers, Ni­[NN]­(η 2 -CS 2 ). , However, in spite of the significant elongation of the metal-bound C–S bond, no C–S bond breaking (or C–C bond formation) was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the Ni{η 2 ‐SC(P n PrPh 2 ) 2 } unit can be compared to the structures of previously studied nickel complexes of carbon disulfide, Ni(η 2 ‐CS 2 )(dtbpe) (dtbpe=1,2‐bis(di‐ tert ‐butyl‐phosphino)ethane and Ni(η 2 ‐CS 2 )(P‐alkenephosphor‐amidite) 2 . In Ni(η 2 ‐CS 2 )(dtbpe) these distances are: Ni−S, 2.147(2) Å; Ni−C, 1.922(5) Å, C−S, 1.732(6) Å . In Ni( η 2 ‐CS 2 )(P‐alkene phosphoramidite) 2 they are: Ni−S, 2.1529(8) Å; Ni−C, 1.913(3) Å; S−C, 1.685(3) Å .…”
Section: Resultsmentioning
confidence: 99%
“…[33] In Ni(h 2 -CS 2 )(dtbpe) these distances are:N i ÀS, 2.147(2) ;N i ÀC, 1.922(5) ,C ÀS, 1.732 (6) . [29,32] In Ni(h 2 -CS 2 )(P-alkene phosphoramidite) 2 they are:N i ÀS, 2.1529 (8) ;N i ÀC, 1.913(3) ;S ÀC, 1.685(3) . [33] There is ap articularlys trong similarity in the h 2 -CSNi units in [Ni{h 2 -SC(P n PrPh 2 ) 2 }Br(P n PrPh 2 )]Br·0.5CS 2 (1)a nd in Ni(h 2 -CS 2 )(dtbpe).…”
Section: Scheme3simple Electronic Structures Of the Ligands In Compomentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17][18] Further transformations of these substrates can be achieved via cleavage of the carbon-sulfur bond, similar to sulfur abstraction observed in low valent transition metal complexes. 34,35 Based on our interest in utilizing reactive metal-carbon bonds for activation of small molecules, [36][37][38][39][40][41][42] we investigated reactions of sulfur containing heteroallenes toward coordinatively unsaturated hydrotris( pyrazolyl)borate nickel(II) alkyl complexes. [22][23][24][25][26][27][28][29] The carbon-sulfur bonds in CS 2 are less susceptible to metal-mediated cleavage, [30][31][32][33] however, and the reactivity of the insertion products is a function of their structures.…”
Section: Introductionmentioning
confidence: 99%